Efficacy of Violet oil, a traditional Iranian formula, in patients with chronic insomnia: A randomized, double-blind, placebo-controlled study. (25th March 2018) - Feyzabadi, Zohre; Rezaeitalab, Fariborz; Badiee, Shapour; Taghipour, Ali; Moharari, Fatemeh; Soltanifar, Atefeh; Ahmadpour, Mohammad Reza
Abstract: Ethnopharmacological relevance: Violet oil is an ancient herbal drug which has been extensively used to treat insomnia in traditional Iranian Medicine clinics. Violet oil is an almond or sesame oil-based extract of Viola odorata, which is administered as nasal drops. This study aimed to evaluate the efficacy of Violet oil in the treatment of insomnia. Methods and materials: This study was conducted as a 3-arm double-blind randomized trial. A total of 75 patients with chronic insomnia were enrolled and randomly assigned to three groups in Traditional Iranian Medicine Clinic of Mashhad University of Medical Sciences, Mashhad, Iran. The treatment consisted of intranasal dropping of Violet oil, Almond oil or placebo (1% solution of Carboxymethyl cellulose) in each nostril every night before sleep for 30 days, i.e. three drops of the drug (including either Violet oil or Almond oil) or the placebo was used every night before the sleep. All the patients were asked to complete Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI) questionnaires before and after the intervention. Results: There were no significant differences between patients in the three groups before the intervention (P > 0.05). However, there were significant differences between the three groups after the intervention in ISI scores (P<0.002) and PSQI scores (p<0.001). When comparing the pre- and post-treatment data, the ISI and PSQI scores improved significantly in all the three groups as follows: Violet oil (P<0.001), Almond oil (P<0.001) and placebo (P<0.001). The results also showed that the Violet oil had the most effect among the three groups. In addition, it was more effective on sleep quality than sleep quantity. Conclusion: Considering the effects of natural nasal drug on the improvement of sleep quality in insomniac patients, this study has proposed the use of Violet oil as a natural and herbal drug in a non-oral method without serious side effects for treatment of insomnia. Graphical abstract: